The Effects of Priming and Ageing on Seed Vigour in Tomato - Argerich, Cosme Alberto (1989)
A comparison was made of the effects of seed priming or ageing treatments on the performance of tomato (Lycopersicon esculentum Mill. cv. UC204C) seeds according to a number of indices of seed vigour. A single lot of tomato seeds was primed in 120 mol m-3 K2HPO4 + 150 mol m-3 KNO3 for 5 d at 20 °C, or aged at 13% moisture content (dry weight basis) and 50 °C for 6 d. Germination percentage (>98%) was unaffected by priming and reduced to 85% by ageing. X-ray photographs and longitudinal sections revealed the formation of free space surrounding the embryo in dry primed seeds, which was not evident in control or aged seeds. Priming increased the rate of germination at all temperatures above the base temperature (Tb), while ageing decreased it. Tb was unaffected by priming and only slightly increased by ageing. The variation in individual times to germination was approximately doubled in both primed and aged seed compared to the control, based upon the slopes of probit germination percentage versus log thermal time curves. Root growth after germination tests and seedling growth in both greenhouse and field tests were not influenced by either priming or ageing. The conductivity test was found to be unreliable as a vigour test for tomato seeds. The results identify several indices which can be used to quantify seed vigour in tomato. They also illustrate that seed priming can enhance seed performance according to some criteria, while having no effect or decreasing quality according to other criteria. Seed vigour can apparently be separated into various components which can be independently influenced by seed enhancement treatments.